Perfil fermentativo de silagens de aveia branca com inoculação de diferentes níveis de aditivo enzimático e microbiano - Klein, Camila (2021)
White Oats can be used both in grain production and in animal feed, in the form of feed or forage (hay, silage, pasture). As these species go through the process of seasonality of production in the winter season, silage is an ideal method of conservation of this forage. In order to improve the fermentation processes of silage, the use of microbial / enzymatic additives acts in reducing the pH through the multiplication of lactic bacteria, in order to reduce losses in dry matter and maintain the nutritive content. The objective of this project was to evaluate the fermentation quality and the losses evaluated in the fermentation process of white oat silage inoculated with enzymatic additive. The oat crop will be implanted in April 2019, and the ensilage process carried out in July and August with cuts in two stages of maturation of the crop, and then stored in micro silos with five levels of microbial / enzymatic additive. . After 42 days the microsilos will be opened and through the collection of the samples, the determinations of pH, buffer capacity, losses (dry matter, gas, effluent and ammoniacal nitrogen) will be made. The experimental design was completely randomized through 5 treatments and 4 repetitions each. As a result, the inoculant doses tested did not result in a significant effect on fermentative parameters and losses in white oat silages, however there was a significant difference for harvest dates.